KAJIAN STRUKTURAL PUISI MANTRA JAMPE NYEURI BEUTEUNG DI SUKU SUNDA - Noor Fadillah; Fitri Nur Amaliyah; Firda Aulia Rahmah; Indrya Mulyaningsih (Jurnal Tradisi Lisan Nusantara, 2023)
Abstract: This study aims to: (1) describe the physical structure of the mantra poem "Jampe Nyeuri Beuteung" in Sundanese culture, (2) describe the inner structure of the mantra poem "Jampe Nyeuri Beuteung" in Sundanese culture. The method of analyzing the research data is descriptive qualitative. The results show that in the Jampe Nyeuri Beuteung mantra poetry there is a physical and mental structure. The physical structure of the mantra includes word choice (diction), figurative language, imagery, rhyme, rhythm, typography. The inner structure of the mantra is the theme of healing, having a weak feeling due to pain, spoken in a tense tone, aiming to treat stomachaches, and the message contains that the person who casts the mantra hopes that he will be given a cure for illness. Poetry as learning material in Indonesian subjects can provide added value in the student learning process.